PENGARUH METODE PEMBELAJARAN SOSIODRAMA TERHADAP HASIL BELAJAR MATERI HUKUM DAGANG PADA MAHASISWA 2014 SESI F PENDIDIKAN EKONOMI STKIP PGRI SUMBAR (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2017)
AbstractThis research was aimed at finding the effect of using the ‘Rules Playing’ method to the result of the learning the students’ learning result in the subject of Economy. The research was a quasi-experiment whose population was grade XI IPS students of 2014 Economic Education STKIP PGRI SUMBAR. The sampling technique used was the purposive sampling. The Sample is Student 2014 F Economic Education STKIP PGRI SUMBAR. The data of the research consisted of two kinds : primary and secondary data. The data were analyzed by using a descriptive method. In the descriptive analysis techniques are the learning outcomes of students who achieve mastery of 80% and which did not achieve mastery of 20%. AbstrakPenelitian ini bertujuan untuk mengungkap mahasiswa yang diajarkan dengan metode sosiodrama memiliki hasil belajar lebih tinggi. Jenis penelitian adalah quasi eksperimen. Populasi penelitian adalah mahasiswa 2014 pendidikan ekonomi STKIP PGRI SUMBAR. Teknik pengambilan sampel adalah Purposive Sampling. Sampel adalah mahasiswa 2014 F pendidikan ekonomi STKIP PGRI SUMBAR. Jenis data terdiri dari data primer dan data sekunder, sedangkan teknik analisis data adalah deskriptif. Pada teknik analisis deskriftif terdapat hasil belajar mahasiswa yang mencapai ketuntasan sebesar 80% dan yang tidak mencapai ketuntasan sebesar 20 %.